Corporate Entrepreneurs or Rogue Middle Managers? A Framework for Ethical Corporate Entrepreneurship - Donald, Kuratko F. (Journal of business ethics, 2004)
Corporate entrepreneurs -- described in the academic literature as those managers or employees who do not follow the status quo of their co-workers -- are depicted as visionaries who dream of taking the company in new directions. As a result, though, in overcoming internal obstacles to reaching their professional goals they can often walk a fine line between clever resourcefulness and outright rule breaking. A framework is presented as a guideline for middle managers and organizations seeking to impede unethical behaviors in the pursuit of entrepreneurial activity. This paper examines the barriers middle managers face in trying to be entrepreneurial in less supportive environments, the ethical consequences that can result, and a suggested assessment and training program for averting such dilemmas. We advise companies that embrace corporate entrepreneurship: (1) establish the needed flexibility, innovation, and employee initiative and risk-taking; (2) remove the barriers that the entrepreneurial middle manager may face to more closely align personal and organizational initiatives and reduce the need to behave unethically; and (3) include an ethical component to corporate training which will provide guidelines for instituting compliance and values components into the state-of-the-art corporate entrepreneurship programs.